(Not) talking about fertility: the role of digital technologies and health services in helping plan pregnancy. A qualitative study. Issue 1 (23rd December 2020) - French, Rebecca S; Shawe, Jill; Tilouche, Nerissa; Earle, Sarah; Grenfell, Pippa
Abstract : Aim: To explore how women and their partners navigate (pre)conception healthcare and the role of Natural Cycles fertility awareness technology in this process. Methods: In-depth interviews with 24 cisgender women aged 24–43 years who had used Natural Cycles' 'Plan a Pregnancy' mode, and six partners of Natural Cycles users, all cisgender men aged 30–39 years. Participants were recruited via direct messaging in the Natural Cycles app, social media and, for partners, snowball sampling. Purposive sampling was conducted to ensure diversity among participants. Interviews were audio-recorded and transcribed verbatim. An iterative, inductive approach was adopted for thematic data analysis. Results: Natural Cycles helped most users better understand their menstrual cycles and fertility. Fertility awareness and preconception counselling with healthcare providers were uncommon. Women felt discussions about planning pregnancy in healthcare settings were often fraught with difficulties. They described not wanting to be an extra burden to overworked staff, being concerned that their worries about trying for pregnancy would be dismissed, or feeling staff did not have expertise in fertility awareness. Some women had shared their Natural Cycles data with healthcare professionals to demonstrate their menstrual cycle data or time of conception. However, it was not always clear to those not accessing services when they should seek further advice, for example, those using the app for longer time periods who had not yet conceived. Conclusions: Digital technologies can provide information and support for those wanting to conceive. They should, however, complement care in statutory services, and be accompanied by greater investment in fertility awareness and preconception support.